Eightieth year of Peking Man: Current status of Peking Man and the Zhoukoudian site - Wang, Qian; Sun, Li (Anthropological Review, 2000)
The current status of and recent developments around Peking Man and Zhoukoudian are reviewed. The taxonomic status, phylogenetic position, cultural attributes and taphonomy of Peking Man are in question, and a new chronological frame for the Zhoukoudian site is emerging. Post-war excavation, current Peking Man specimens, the research unit, personalities, commemoration, and classic books are introduced, with special reference to the search for the long-missing Peking Man fossils.